Cyanine dye excimer formation in nanoporou SiO₂ matrices - Gnap, B.A.; Bespalova, I.I.; Yefimova, S.L.; Sorokin, A.V. (Functional Materials, 2013)
Novel red-shifted band has been observed in luminescence spectra of a cyanine dye embedded into nanoporous SiO₂ matrix.